O4C.3 Job strain, exposure to carcinogens and the wellbeing of migrant workers. (April 2019) - Daly, Alison; Reid, Alison
Abstract : Introduction: Job strain adversely affects wellbeing. It is unclear if job strain increases the risk of exposure to carcinogens. The aim of this study is to examine how high strain jobs influence exposure to carcinogens and wellbeing and whether this varies by migration status. Methods: A national telephone survey conducted in 2016/17 examined exposure to workplace hazards among 1630 migrant workers (born in India, New Zealand and the Philippines). Exposure to carcinogens was assessed an online platform that automates exposure assessment. High job strain and wellbeing was measured using standardised questionnaires. Univariate statistics examined high job strain and exposure to carcinogens by country of birth. Models were developed to explore these associations. Results: There were no differences in prevalence of job strain by country of birth with percents ranging from 23.8% [95% CI 18.6, 30.0] for India-born workers to 26.5% [95% 21.7, 31.8] for New Zealand-born. A lower percent of migrants born in India or the Philippines were exposed to any carcinogens at work 55.2% [95% CI 51.2, 59.0]) compared New Zealand workers (68.8% [95% CI 63.9, 73.4] vs 55.2% [95% CI 51.2, 59.0]). Wellness means ranged from 13.6 [95% CI 13.1, 14.1] for Philippines-born workers to 14.3 [95% CI 13.9, 14.7] for New Zealand-born. Wellbeing was adversely impacted by high job strain (Coef=2.1 95% CI 1.7, 2.6). There was no difference by country of birth. Job strain was not associated with exposure to carcinogens but country of birth was with workers born in India having a lower probability of being exposed (Predicted probability of exposure:. 50 (95% CI. 46, .54) compared with the other migrant workers. Discussion: High strain jobs adversely affected wellbeing independent of migrant status. Job strain was not associated with either exposure to carcinogens or migrant status. However migrant status was associated with exposure to carcinogens.